A heat insulation powder for a nuclear reactor thermal system box and a preparation method thereof

CN118448072BActive Publication Date: 2026-11-03NUCLEAR POWER INSTITUTE OF CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410512598.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-26
Publication Date
2026-11-03
Estimated Expiration
2044-04-26

AI Technical Summary

Technical Problem

现有金属反射型保温层在高温服役环境下隔热性能下降,存在漏热及烟卤效应,且二氧化硅气凝胶在3~8μm波长范围内热辐射透明,导致隔热性能不足。

Method used

A combination of nano-silica aerogel, metal co-doped solid solution opaque agent powder, and inorganic heat insulation powder is used to improve heat insulation performance by increasing the lattice interface of infrared opaque agent particles and phonon scattering, thereby inhibiting heat conduction and forming a disordered solid solution.

Benefits of technology

It effectively suppresses radiative heat transfer, convective heat transfer, and solid-phase heat conduction, improving the insulation effect of the box-type insulation of the nuclear reactor thermal system, while also being economical and having neutron ray shielding function.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of nuclear reactor thermodynamic system box type heat preservation heat insulation powder and preparation method thereof, relate to heat preservation heat insulation material technical field, raw material component includes nanometer silica aerogel, metal co-doped solid solution sunscreen powder, inorganic heat insulation powder;According to mass percentage, the amount of nanometer silica aerogel is 10%~80%, the amount of metal co-doped solid solution sunscreen powder is 0~10%, and the amount of inorganic heat insulation powder is 20%~80%.By metal doping to form disordered solid solution, increase the phonon scattering of infrared sunscreen particle lattice interface and defect to inhibit heat conduction, so as to further improve the overall thermal insulation performance of heat insulation powder, the box type heat preservation piece made after powder filling has inhibitory effect on radiation heat transfer, convection heat transfer and solid phase heat conduction, and then the heat insulation effect can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermal insulation materials, specifically to a thermal insulation powder for box-type thermal insulation of a nuclear reactor thermal system and its preparation method. Background Technology

[0002] Nuclear reactor systems operate in high-temperature, high-pressure, and high-radiation environments. Their thermal system equipment and piping require insulation layers to reduce system heat loss, thereby improving the power generation efficiency and economic benefits of the nuclear power plant. Currently, the main equipment and piping of third-generation nuclear power units mostly use metal reactive insulation. This metal insulation layer is an air-cavity reflective insulation structure, made entirely of stainless steel. Multiple layers of stainless steel foil are filled within the metal shell to form individual insulation blocks, and the entire insulation layer is composed of several interconnected insulation blocks. Metal reactive insulation layers have advantages such as radiation resistance, dust-free operation, and easy cleaning. However, under long-term high-temperature service conditions, the metal reflective foil is prone to passivation, leading to a decrease in its thermal insulation performance. It also suffers from problems such as heat leakage at joints and halogen effects. Therefore, traditional metal reflective insulation layers have certain limitations.

[0003] Nuclear reactor powder-filled box-type insulation uses insulating powder to replace the metal reflective foil inside the traditional metal insulation layer, thereby improving its heat insulation performance and thermal stability. Simultaneously, heat-insulating pads are added at the joints of the insulation blocks to prevent heat leakage. In the box-type insulation structure, the insulating powder bears the main heat insulation function, and its quality directly affects the overall heat insulation effect of the insulation structure.

[0004] Silica aerogel is currently the powder material with the best thermal insulation performance. It possesses open nanopores and a spatially continuous network structure. The nanoscale network pore structure restricts air convection, thus exhibiting excellent thermal insulation properties. However, silica aerogel is almost transparent to thermal radiation in the 3–8 μm wavelength range. According to Planck's law of blackbody radiation, the thermal radiation temperature range corresponding to the 3–8 μm wavelength is approximately 90–700 °C, covering the operating temperature of pressurized water reactors (approximately 300 °C). This causes the aerogel to lose its super-insulating properties due to prominent radiative heat transfer during high-temperature operations. Adding dielectric particles with high infrared spectral attenuation coefficients to the aerogel powder can limit its internal radiative heat transfer. Common infrared shielding agents include ceramic-based particles such as titanium dioxide, potassium hexatitanate, silicon carbide, and boron carbide. However, most ceramic-based fillers have crystalline regions, resulting in weak phonon scattering and significant thermal conductivity. Summary of the Invention

[0005] Based on the problems in the background art, the purpose of this invention is to provide a heat insulation powder for box-type insulation of nuclear reactor thermal systems and its preparation method. The heat insulation powder material has good high-temperature heat insulation performance and economy, and also meets the requirements of nuclear reactor application environment such as radiation resistance, fire prevention and radiation shielding.

[0006] This invention is achieved through the following technical solution:

[0007] In a first aspect, this application provides a heat-insulating powder for box-type thermal insulation of a nuclear reactor thermal system. The raw material composition includes nano-silica aerogel, metal co-doped solid solution opacifier powder, and inorganic heat-insulating powder. By mass percentage, the amount of nano-silica aerogel is 10% to 80%, the amount of metal co-doped solid solution opacifier powder is 0% to 10%, and the amount of inorganic heat-insulating powder is 20% to 80%.

[0008] This application forms a disordered solid solution by metal doping, which increases phonon scattering at the lattice interface and defects of infrared shading agent particles to suppress heat conduction, thereby further improving the overall heat insulation performance of the heat insulation powder. The box-type heat insulation component made after the powder is filled has the effect of suppressing radiative heat transfer, convective heat transfer and solid phase heat conduction at the same time, thus effectively improving the heat insulation effect.

[0009] According to the theory of microscopic thermal conductivity, the effective thermal conductivity of insulation materials comprises three parts: convective heat transfer, radiative heat transfer, and solid-phase heat transfer. The carriers of convective heat transfer are molecules, those of radiative heat transfer are photons, and those of solid-phase heat transfer are phonons or electrons. In this invention, the network structure of nano-silica aerogel separates air into countless small pores with diameters ranging from 1 to 100 nm, while the free path of air is approximately 70 nm. Therefore, these pores significantly restrict convective heat transfer. The metal co-doped solid solution opacifier powder effectively suppresses solid-phase heat transfer by enhancing phonon scattering at lattice interfaces and defects. Furthermore, the selected components have a large spectral attenuation coefficient for infrared electromagnetic waves, effectively compensating for the radiative heat transfer defects present in aerogel powder at medium to high temperatures. In summary, the insulating powder provides excellent insulation against all three types of heat transfer: radiation, convection, and conduction. Therefore, the insulating powder for box-type insulation of nuclear reactor thermal systems in this application possesses excellent thermal insulation performance.

[0010] The inorganic heat insulation powder added in this application can improve the economy and filling performance of heat insulation powder for box-type insulation. At the same time, when the heat insulation powder is made of materials containing boron carbide, it has a certain shielding function against neutron rays in the nuclear reactor environment.

[0011] Furthermore, the preparation method of the nano-silica aerogel includes the following steps:

[0012] Using tetraethyl orthosilicate as the silicon source, ethanol was added to tetraethyl orthosilicate and mixed. Then, H2O was added dropwise under mechanical stirring, and 0.05% to 0.2% salt water was added dropwise and stirred. After being sealed and allowed to stand at room temperature, SiO2 sol was obtained.

[0013] Add 0.1% to 0.3% ammonia water to SiO2 sol, stir evenly, and let stand to form a gel to obtain SiO2 alcohol sol;

[0014] After the SiO2 alcohol sol is sealed and aged, a complete nano-silica aerogel is obtained through a supercritical fluid drying process.

[0015] Furthermore, the preparation method of the metal co-doped solid solution opacifier powder includes the following steps:

[0016] Select several of the following as precursors: titanium nitrate, nickel nitrate, iron nitrate, and lanthanum nitrate. Weigh them according to a certain molar ratio and prepare a solution.

[0017] The prepared precursor solution is thoroughly stirred and reacted to form a sol.

[0018] The sol is heated and kept at a constant temperature, then evaporated and dried to form a gel.

[0019] The obtained gel was calcined, then ground and sieved to obtain uniformly sized metal co-doped solid solution opacifier powder.

[0020] Furthermore, the inorganic heat-insulating powder includes any one or a combination of several of the following: perlite, vitrified microspheres, and perlite.

[0021] Furthermore, the average particle size of the nano-silica aerogel is no greater than 50 nm, and the specific surface area is no less than 200 m². 2 / g, thermal stability temperature not lower than 500℃.

[0022] Furthermore, this also includes radiation shielding powder.

[0023] Furthermore, the radiation shielding powder includes any one or a combination of boron carbide, boron nitride, tungsten powder, and bismuth oxide; preferably, it is boron carbide powder.

[0024] Furthermore, the metal co-doped solid solution opacifier powder is titanium oxide powder that has undergone elemental doping.

[0025] Furthermore, the doping elements include any one or more of nickel, lanthanum, iron, barium, tungsten, zinc, magnesium, and cobalt.

[0026] Secondly, this application provides a method for preparing heat-insulating powder for box-type thermal insulation of nuclear reactor thermal systems. The heat-insulating powder material for box-type thermal insulation is obtained by uniformly mixing nano-silica aerogel, metal co-doped solid solution opacifier powder, inorganic heat-insulating powder, and radiation shielding powder.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] (1) This application forms a disordered solid solution by metal doping, increases phonon scattering at the lattice interface and defects of infrared shading agent particles to suppress heat conduction, thereby further improving the overall heat insulation performance of the heat insulation powder. The box-type heat insulation component made after the powder is filled has the effect of suppressing radiation heat transfer, convective heat transfer and solid phase heat conduction at the same time, thus effectively improving the heat insulation effect.

[0029] (2) In this invention, the network structure of the nano-silica aerogel separates the air into countless small pores with diameters ranging from 1 to 100 nm, while the free path of air is approximately 70 nm. Therefore, these pores greatly restrict the convective heat transfer of the air. The metal co-doped solid solution opacifier powder effectively suppresses solid-phase heat conduction by improving phonon scattering at lattice interfaces and lattice defects. At the same time, the selected components have a large spectral attenuation coefficient for infrared electromagnetic waves, effectively compensating for the radiative heat transfer defects of aerogel powder at medium and high temperatures. In summary, the heat-insulating powder has a good insulating effect on all three types of heat transfer: thermal radiation, thermal convection, and thermal conduction. Therefore, the heat-insulating powder for box-type insulation of nuclear reactor thermal systems in this application has good heat insulation performance.

[0030] (3) The inorganic heat insulation powder added in this application can improve the economy and filling performance of the heat insulation powder for box insulation. At the same time, when the heat insulation powder is made of materials containing boron carbide, it has a certain shielding function against neutron rays in the nuclear reactor environment. Detailed Implementation

[0031] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.

[0032] In the following description, numerous specific details are set forth in order to provide a thorough understanding of the invention. However, it will be apparent to those skilled in the art that these specific details are not necessary to practice the invention. In other embodiments, well-known materials or methods have not been specifically described in order to avoid obscuring the invention.

[0033] Throughout this specification, references to "an embodiment," "an example," or "an example" mean that a particular feature or characteristic described in connection with that embodiment or example is included in at least one embodiment of the invention. Therefore, the phrases "an embodiment," "an example," "an example," or "an example" appearing in various places throughout the specification do not necessarily refer to the same embodiment or example. Furthermore, specific features, structures, or characteristics can be combined in one or more embodiments or examples in any suitable combination and / or sub-combination. Moreover, those skilled in the art will understand that the term "and / or" as used includes any and all combinations of one or more of the associated listed items.

[0034] Therefore, the following detailed description of embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0035] Example 1

[0036] This embodiment provides a method for preparing heat-insulating powder for box-type insulation of nuclear reactor thermal systems, the specific steps of which are as follows:

[0037] S1: Using tetraethyl orthosilicate as the silicon source, ethanol was added to the silicon source at a molar ratio of 1:8. Then, H2O was added dropwise under mechanical stirring, followed by the addition of 0.1% hydrochloric acid. After stirring for 20 minutes, the mixture was sealed and allowed to stand at room temperature for 24 hours to obtain silica sol.

[0038] S2: Add 0.2% ammonia water to silica sol, stir evenly, and let stand to form a gel to obtain silica alcohol gel;

[0039] S3: After sealing and aging, silica alcohol gel is prepared by supercritical fluid drying process to produce gels with a specific surface area between 200 and 1100 m². 2 / g, with particle size between 5 and 28 nm and average pore size between 7 and 22 nm;

[0040] S4: Select 500g of nano-silica aerogel powder, 450g of vitrified microspheres, and 50g of boron carbide and mix them in a mixer for 2 hours to obtain heat insulation powder for box-type insulation.

[0041] The prepared box-type insulation powder was uniformly filled into a stainless steel box, and the opening was sealed to obtain a powder-filled box-type insulation block. According to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method", the effective thermal conductivity of the box-type insulation block at a hot surface temperature of 300℃ was measured to be 0.050 W / (m·K) using a high-temperature thermal conductivity tester.

[0042] Example 2

[0043] This embodiment provides a method for preparing heat-insulating powder for box-type insulation of nuclear reactor thermal systems, the specific steps of which are as follows:

[0044] S1: Using tetraethyl orthosilicate as the silicon source, ethanol was added to the silicon source at a molar ratio of 1:8. Then, H2O was added dropwise under mechanical stirring, followed by the addition of 0.1% hydrochloric acid. After stirring for 20 minutes, the mixture was sealed and allowed to stand at room temperature for 24 hours to obtain silica sol.

[0045] S2: Add 0.2% ammonia water to silica sol, stir evenly, and let stand to form a gel to obtain silica alcohol gel;

[0046] S3: After sealing and aging, silica alcohol gel is prepared by supercritical fluid drying process to produce gels with a specific surface area between 200 and 1100 m². 2 / g, with particle size between 5 and 28 nm and average pore size between 7 and 22 nm;

[0047] S4: Select 500g of nano-silica aerogel powder, 450g of perlite, and 50g of boron carbide and mix them in a mixer for 2 hours to obtain heat insulation powder for box-type insulation.

[0048] The prepared box-type insulation powder was uniformly filled into a stainless steel box, and the opening was sealed to obtain a powder-filled box-type insulation block. According to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method", the effective thermal conductivity of the box-type insulation block at a hot surface temperature of 300℃ was measured to be 0.048 W / (m·K) using a high-temperature thermal conductivity tester.

[0049] Example 3

[0050] This embodiment provides a method for preparing heat-insulating powder for box-type insulation of nuclear reactor thermal systems, the specific steps of which are as follows:

[0051] S1: Using tetraethyl orthosilicate as the silicon source, ethanol was added to the silicon source at a molar ratio of 1:8. Then, H2O was added dropwise under mechanical stirring, followed by 0.1% hydrochloric acid. After stirring for 20 minutes, the mixture was sealed and allowed to stand at room temperature for 24 hours to obtain silica sol.

[0052] S2: Add 0.2% ammonia water to silica sol, stir evenly, and let stand to form a gel to obtain silica alcohol gel;

[0053] S3: After sealing and aging, silica alcohol gel is prepared by supercritical fluid drying process to produce gels with a specific surface area between 200 and 1100 m². 2 / g, with particle size between 5 and 28 nm and average pore size between 7 and 22 nm;

[0054] S4: Weigh titanium nitrate, nickel nitrate, and lanthanum nitrate in a molar ratio of 8:1:1, add them to water to prepare a solution, mix and stir, put the solution into an oven preheated to 160°C to dry, then calcine it in a high-temperature furnace at 1100°C for 1 hour, and then grind it to obtain nickel-lanthanum co-doped titanium oxide infrared shielding agent powder.

[0055] S5: Select 500g of nano-silica aerogel, 400g of perlite, 50g of boron carbide, and 50g of nickel-lanthanum co-doped titanium dioxide infrared shading agent powder, mix them in a mixer for 2 hours to obtain heat insulation powder for box-type thermal insulation.

[0056] The heat-insulating powder for box-type insulation prepared in this embodiment was uniformly filled into a stainless steel box, and the opening was sealed to obtain a powder-filled box-type insulation block. According to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method", the effective thermal conductivity of the above-mentioned box-type insulation block at a hot surface temperature of 300℃ was measured to be 0.042 W / (m·K) using a high-temperature thermal conductivity tester.

[0057] Example 4

[0058] This embodiment provides a method for preparing heat-insulating powder for box-type insulation of nuclear reactor thermal systems, the specific steps of which are as follows:

[0059] S1: Using tetraethyl orthosilicate as the silicon source, ethanol was added to the silicon source at a molar ratio of 1:8. Then, H2O was added dropwise under mechanical stirring, followed by 0.1% hydrochloric acid. After stirring for 20 minutes, the mixture was sealed and allowed to stand at room temperature for 24 hours to obtain silica sol.

[0060] S2: Add 0.2% ammonia water to silica sol, stir evenly, and let stand to form a gel to obtain silica alcohol gel;

[0061] S3: After sealing and aging, silica alcohol gel is prepared by supercritical fluid drying process to produce gels with a specific surface area between 200 and 1100 m². 2 / g, with particle size between 5 and 28 nm and average pore size between 7 and 22 nm;

[0062] S4: Weigh titanium nitrate, nickel nitrate, and lanthanum nitrate in a molar ratio of 8:1:1, add them to water to prepare a solution, mix and stir, put the solution into an oven preheated to 160°C to dry, then calcine it in a high-temperature furnace at 1100°C for 1 hour, and then grind it to obtain nickel-lanthanum co-doped titanium oxide infrared shielding agent powder.

[0063] S5: Select 500g of nano-silica aerogel, 350g of perlite, 50g of boron carbide, and 100g of nickel-lanthanum co-doped titanium dioxide infrared shading agent powder, mix them in a mixer for 2 hours to obtain heat insulation powder for box-type thermal insulation.

[0064] The heat-insulating powder for box-type insulation prepared in this embodiment was uniformly filled into a stainless steel box, and the opening was sealed to obtain a powder-filled box-type insulation block. According to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method", the effective thermal conductivity of the above-mentioned box-type insulation block at a hot surface temperature of 300℃ was measured to be 0.039 W / (m·K) using a high-temperature thermal conductivity tester.

[0065] Example 5

[0066] This embodiment provides a method for preparing heat-insulating powder for box-type insulation of nuclear reactor thermal systems. Unlike Embodiment 4, the amount of hydrochloric acid added in this embodiment is 0.05%. The specific steps are as follows:

[0067] S1: Using tetraethyl orthosilicate as the silicon source, ethanol was added to the silicon source at a molar ratio of 1:8. Then, H2O was added dropwise under mechanical stirring, and 0.05% hydrochloric acid was added dropwise. After stirring for 20 minutes, the mixture was sealed and allowed to stand at room temperature for 24 hours to obtain silica sol.

[0068] S2: Add 0.2% ammonia water to silica sol, stir evenly, and let stand to form a gel to obtain silica alcohol gel;

[0069] S3: After sealing and aging, silica alcohol gel is prepared by supercritical fluid drying process to produce gels with a specific surface area between 200 and 1100 m². 2 / g, with particle size between 5 and 28 nm and average pore size between 7 and 22 nm;

[0070] S4: Weigh titanium nitrate, nickel nitrate, and lanthanum nitrate in a molar ratio of 8:1:1, add them to water to prepare a solution, mix and stir, put the solution into an oven preheated to 160°C to dry, then calcine it in a high-temperature furnace at 1100°C for 1 hour, and then grind it to obtain nickel-lanthanum co-doped titanium oxide infrared shielding agent powder.

[0071] S5: Select 500g of nano-silica aerogel, 350g of perlite, 50g of boron carbide, and 100g of nickel-lanthanum co-doped titanium dioxide infrared shading agent powder, mix them in a mixer for 2 hours to obtain heat insulation powder for box-type thermal insulation.

[0072] The heat-insulating powder for box-type insulation prepared in this embodiment was uniformly filled into a stainless steel box, and the opening was sealed to obtain a powder-filled box-type insulation block. According to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method", the effective thermal conductivity of the above-mentioned box-type insulation block at a hot surface temperature of 300℃ was measured to be 0.039 W / (m·K) using a high-temperature thermal conductivity tester.

[0073] Example 6

[0074] This embodiment provides a method for preparing heat-insulating powder for box-type insulation of nuclear reactor thermal systems. Unlike Embodiment 4, the amount of hydrochloric acid added in this embodiment is 0.2%. The specific steps are as follows:

[0075] S1: Using tetraethyl orthosilicate as the silicon source, ethanol was added to the silicon source at a molar ratio of 1:8. Then, H2O was added dropwise under mechanical stirring, followed by 0.2% hydrochloric acid. After stirring for 20 minutes, the mixture was sealed and allowed to stand at room temperature for 24 hours to obtain silica sol.

[0076] S2: Add 0.2% ammonia water to silica sol, stir evenly, and let stand to form a gel to obtain silica alcohol gel;

[0077] S3: After sealing and aging, silica alcohol gel is prepared by supercritical fluid drying process to produce gels with a specific surface area between 200 and 1100 m². 2 / g, with particle size between 5 and 28 nm and average pore size between 7 and 22 nm;

[0078] S4: Weigh titanium nitrate, nickel nitrate, and lanthanum nitrate in a molar ratio of 8:1:1, add them to water to prepare a solution, mix and stir, put the solution into an oven preheated to 160°C to dry, then calcine it in a high-temperature furnace at 1100°C for 1 hour, and then grind it to obtain nickel-lanthanum co-doped titanium oxide infrared shielding agent powder.

[0079] S5: Select 500g of nano-silica aerogel, 350g of perlite, 50g of boron carbide, and 100g of nickel-lanthanum co-doped titanium dioxide infrared shading agent powder, mix them in a mixer for 2 hours to obtain heat insulation powder for box-type thermal insulation.

[0080] The heat-insulating powder for box-type insulation prepared in this embodiment was uniformly filled into a stainless steel box, and the opening was sealed to obtain a powder-filled box-type insulation block. According to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method", the effective thermal conductivity of the above-mentioned box-type insulation block at a hot surface temperature of 300℃ was measured to be 0.040 W / (m·K) using a high-temperature thermal conductivity tester.

[0081] Example 7

[0082] This embodiment provides a method for preparing heat-insulating powder for box-type insulation of nuclear reactor thermal systems. Unlike Embodiment 4, the amount of ammonia water added in this embodiment is 0.1%. The specific steps are as follows:

[0083] S1: Using tetraethyl orthosilicate as the silicon source, ethanol was added to the silicon source at a molar ratio of 1:8. Then, H2O was added dropwise under mechanical stirring, followed by the addition of 0.1% hydrochloric acid. After stirring for 20 minutes, the mixture was sealed and allowed to stand at room temperature for 24 hours to obtain silica sol.

[0084] S2: Add 0.1% ammonia water to silica sol, stir evenly, and let stand to form a gel to obtain silica alcohol gel;

[0085] S3: After sealing and aging, silica alcohol gel is prepared by supercritical fluid drying process to produce gels with a specific surface area between 200 and 1100 m². 2 / g, with particle size between 5 and 28 nm and average pore size between 7 and 22 nm;

[0086] S4: Weigh titanium nitrate, nickel nitrate, and lanthanum nitrate in a molar ratio of 8:1:1, add them to water to prepare a solution, mix and stir, put the solution into an oven preheated to 160°C to dry, then calcine it in a high-temperature furnace at 1100°C for 1 hour, and then grind it to obtain nickel-lanthanum co-doped titanium oxide infrared shielding agent powder.

[0087] S5: Select 500g of nano-silica aerogel, 350g of perlite, 50g of boron carbide, and 100g of nickel-lanthanum co-doped titanium dioxide infrared shading agent powder, mix them in a mixer for 2 hours to obtain heat insulation powder for box-type thermal insulation.

[0088] The heat-insulating powder for box-type insulation prepared in this embodiment was uniformly filled into a stainless steel box, and the opening was sealed to obtain a powder-filled box-type insulation block. According to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method", the effective thermal conductivity of the above-mentioned box-type insulation block at a hot surface temperature of 300℃ was measured to be 0.039 W / (m·K) using a high-temperature thermal conductivity tester.

[0089] Example 8

[0090] This embodiment provides a method for preparing heat-insulating powder for box-type insulation of nuclear reactor thermal systems. Unlike Embodiment 4, the amount of ammonia water added in this embodiment is 0.3%. The specific steps are as follows:

[0091] S1: Using tetraethyl orthosilicate as the silicon source, ethanol was added to the silicon source at a molar ratio of 1:8. Then, H2O was added dropwise under mechanical stirring, followed by the addition of 0.1% hydrochloric acid. After stirring for 20 minutes, the mixture was sealed and allowed to stand at room temperature for 24 hours to obtain silica sol.

[0092] S2: Add 0.3% ammonia water to silica sol, stir evenly, and let stand to form a gel to obtain silica alcohol gel;

[0093] S3: After sealing and aging, silica alcohol gel is prepared by supercritical fluid drying process to produce gels with a specific surface area between 200 and 1100 m². 2 / g, with particle size between 5 and 28 nm and average pore size between 7 and 22 nm;

[0094] S4: Weigh titanium nitrate, nickel nitrate, and lanthanum nitrate in a molar ratio of 8:1:1, add them to water to prepare a solution, mix and stir, put the solution into an oven preheated to 160°C to dry, then calcine it in a high-temperature furnace at 1100°C for 1 hour, and then grind it to obtain nickel-lanthanum co-doped titanium oxide infrared shielding agent powder.

[0095] S5: Select 500g of nano-silica aerogel, 350g of perlite, 50g of boron carbide, and 100g of nickel-lanthanum co-doped titanium dioxide infrared shading agent powder, mix them in a mixer for 2 hours to obtain heat insulation powder for box-type thermal insulation.

[0096] The heat-insulating powder for box-type insulation prepared in this embodiment was uniformly filled into a stainless steel box, and the opening was sealed to obtain a powder-filled box-type insulation block. According to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method", the effective thermal conductivity of the above-mentioned box-type insulation block at a hot surface temperature of 300℃ was measured to be 0.038 W / (m·K) using a high-temperature thermal conductivity tester.

[0097] Example 9

[0098] This embodiment provides a method for preparing heat-insulating powder for box-type insulation of nuclear reactor thermal systems. Unlike Embodiment 4, the inorganic heat-insulating powder in this embodiment is perlite. The specific steps are as follows:

[0099] S1: Using tetraethyl orthosilicate as the silicon source, ethanol was added to the silicon source at a molar ratio of 1:8. Then, H2O was added dropwise under mechanical stirring, followed by the addition of 0.1% hydrochloric acid. After stirring for 20 minutes, the mixture was sealed and allowed to stand at room temperature for 24 hours to obtain silica sol.

[0100] S2: Add 0.2% ammonia water to silica sol, stir evenly, and let stand to form a gel to obtain silica alcohol gel;

[0101] S3: After sealing and aging, silica alcohol gel is prepared by supercritical fluid drying process to produce gels with a specific surface area between 200 and 1100 m². 2 / g, with particle size between 5 and 28 nm and average pore size between 7 and 22 nm;

[0102] S4: Weigh titanium nitrate, nickel nitrate, and lanthanum nitrate in a molar ratio of 8:1:1, add them to water to prepare a solution, mix and stir, put the solution into an oven preheated to 160°C to dry, then calcine it in a high-temperature furnace at 1100°C for 1 hour, and then grind it to obtain nickel-lanthanum co-doped titanium oxide infrared shielding agent powder.

[0103] S5: Select 500g of nano-silica aerogel, 350g of perlite, 50g of boron carbide, and 100g of nickel-lanthanum co-doped titanium dioxide infrared shading agent powder, mix them in a mixer for 2 hours to obtain heat insulation powder for box-type thermal insulation.

[0104] The heat-insulating powder for box-type insulation prepared in this embodiment was uniformly filled into a stainless steel box, and the opening was sealed to obtain a powder-filled box-type insulation block. According to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method", the effective thermal conductivity of the above-mentioned box-type insulation block at a hot surface temperature of 300℃ was measured to be 0.040 W / (m·K) using a high-temperature thermal conductivity tester.

[0105] Example 10

[0106] This embodiment provides a method for preparing heat-insulating powder for box-type insulation of nuclear reactor thermal systems. Unlike Embodiment 4, the radiation-shielding powder in this embodiment is boron nitride. The specific steps are as follows:

[0107] S1: Using tetraethyl orthosilicate as the silicon source, ethanol was added to the silicon source at a molar ratio of 1:8. Then, H2O was added dropwise under mechanical stirring, and 0.05% hydrochloric acid was added dropwise. After stirring for 20 minutes, the mixture was sealed and allowed to stand at room temperature for 24 hours to obtain silica sol.

[0108] S2: Add 0.2% ammonia water to silica sol, stir evenly, and let stand to form a gel to obtain silica alcohol gel;

[0109] S3: After sealing and aging, silica alcohol gel is prepared by supercritical fluid drying process to produce gels with a specific surface area between 200 and 1100 m². 2 / g, with particle size between 5 and 28 nm and average pore size between 7 and 22 nm;

[0110] S4: Weigh titanium nitrate, nickel nitrate, and lanthanum nitrate in a molar ratio of 8:1:1, add them to water to prepare a solution, mix and stir, put the solution into an oven preheated to 160°C to dry, then calcine it in a high-temperature furnace at 1100°C for 1 hour, and then grind it to obtain nickel-lanthanum co-doped titanium oxide infrared shielding agent powder.

[0111] S5: Select 500g of nano-silica aerogel, 350g of perlite, 50g of boron nitride, and 100g of nickel-lanthanum co-doped titanium dioxide infrared shading agent powder, mix them in a mixer for 2 hours to obtain heat insulation powder for box-type thermal insulation.

[0112] The heat-insulating powder for box-type insulation prepared in this embodiment was uniformly filled into a stainless steel box, and the opening was sealed to obtain a powder-filled box-type insulation block. According to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method", the effective thermal conductivity of the above-mentioned box-type insulation block at a hot surface temperature of 300℃ was measured to be 0.042 W / (m·K) using a high-temperature thermal conductivity tester.

[0113] Example 11

[0114] This embodiment provides a method for preparing heat-insulating powder for box-type insulation of nuclear reactor thermal systems. Unlike Embodiment 4, the radiation-shielding powder in this embodiment is tungsten powder. The specific steps are as follows:

[0115] S1: Using tetraethyl orthosilicate as the silicon source, ethanol was added to the silicon source at a molar ratio of 1:8. Then, H2O was added dropwise under mechanical stirring, and 0.05% hydrochloric acid was added dropwise. After stirring for 20 minutes, the mixture was sealed and allowed to stand at room temperature for 24 hours to obtain silica sol.

[0116] S2: Add 0.2% ammonia water to silica sol, stir evenly, and let stand to form a gel to obtain silica alcohol gel;

[0117] S3: After sealing and aging, silica alcohol gel is prepared by supercritical fluid drying process to produce gels with a specific surface area between 200 and 1100 m². 2 / g, with particle size between 5 and 28 nm and average pore size between 7 and 22 nm;

[0118] S4: Weigh titanium nitrate, nickel nitrate, and lanthanum nitrate in a molar ratio of 8:1:1, add them to water to prepare a solution, mix and stir, put the solution into an oven preheated to 160°C to dry, then calcine it in a high-temperature furnace at 1100°C for 1 hour, and then grind it to obtain nickel-lanthanum co-doped titanium oxide infrared shielding agent powder.

[0119] S5: Select 500g of nano-silica aerogel, 350g of perlite, 50g of tungsten powder, and 100g of nickel-lanthanum co-doped titanium dioxide infrared shading agent powder, mix them in a mixer for 2 hours to obtain heat insulation powder for box-type insulation.

[0120] The heat-insulating powder for box-type insulation prepared in this embodiment was uniformly filled into a stainless steel box, and the opening was sealed to obtain a powder-filled box-type insulation block. According to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method", the effective thermal conductivity of the above-mentioned box-type insulation block at a hot surface temperature of 300℃ was measured to be 0.050 W / (m·K) using a high-temperature thermal conductivity tester.

[0121] Example 12

[0122] This embodiment provides a method for preparing heat-insulating powder for box-type insulation of nuclear reactor thermal systems. Unlike Embodiment 4, the radiation-shielding powder in this embodiment is bismuth oxide. The specific steps are as follows:

[0123] S1: Using tetraethyl orthosilicate as the silicon source, ethanol was added to the silicon source at a molar ratio of 1:8. Then, H2O was added dropwise under mechanical stirring, and 0.05% hydrochloric acid was added dropwise. After stirring for 20 minutes, the mixture was sealed and allowed to stand at room temperature for 24 hours to obtain silica sol.

[0124] S2: Add 0.2% ammonia water to silica sol, stir evenly, and let stand to form a gel to obtain silica alcohol gel;

[0125] S3: After sealing and aging, silica alcohol gel is prepared by supercritical fluid drying process to produce gels with a specific surface area between 200 and 1100 m². 2 / g, with particle size between 5 and 28 nm and average pore size between 7 and 22 nm;

[0126] S4: Weigh titanium nitrate, nickel nitrate, and lanthanum nitrate in a molar ratio of 8:1:1, add them to water to prepare a solution, mix and stir, put the solution into an oven preheated to 160°C to dry, then calcine it in a high-temperature furnace at 1100°C for 1 hour, and then grind it to obtain nickel-lanthanum co-doped titanium oxide infrared shielding agent powder.

[0127] S5: Select 500g of nano-silica aerogel, 350g of perlite, 50g of bismuth oxide, and 100g of nickel-lanthanum co-doped titanium dioxide infrared shading agent powder, mix them in a mixer for 2 hours to obtain heat insulation powder for box-type thermal insulation.

[0128] The heat-insulating powder for box-type insulation prepared in this embodiment was uniformly filled into a stainless steel box, and the opening was sealed to obtain a powder-filled box-type insulation block. According to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method", the effective thermal conductivity of the above-mentioned box-type insulation block at a hot surface temperature of 300℃ was measured to be 0.045 W / (m·K) using a high-temperature thermal conductivity tester.

[0129] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A heat-insulating powder for box-type insulation of a nuclear reactor thermal system, characterized in that, The raw material composition includes nano-silica aerogel, metal co-doped solid solution opacifier powder, and inorganic heat insulation powder; by mass percentage, the amount of nano-silica aerogel is 10%~80%, the amount of metal co-doped solid solution opacifier powder is 0~10%, and the amount of inorganic heat insulation powder is 20%~80%. The metal co-doped solid solution opacifier powder forms a disordered solid solution through metal doping, thereby increasing phonon scattering at the lattice interfaces and defects of the infrared opacifier particles and suppressing heat conduction.

2. The heat-insulating powder for box-type insulation of a nuclear reactor thermal system according to claim 1, characterized in that, The preparation method of the nano-silica aerogel includes the following steps: Using tetraethyl orthosilicate as the silicon source, ethanol was added to tetraethyl orthosilicate and mixed. Then, H2O was added dropwise under mechanical stirring, and 0.05%~0.2% salt water was added dropwise and stirred. After being sealed and allowed to stand at room temperature, SiO2 sol was obtained. Add 0.1%~0.3% ammonia water to SiO2 sol, stir evenly, and let stand to form a gel to obtain SiO2 alcohol sol; After the SiO2 alcohol sol is sealed and aged, a complete nano-silica aerogel is obtained through a supercritical fluid drying process.

3. The heat-insulating powder for box-type insulation of a nuclear reactor thermal system according to claim 1, characterized in that, The preparation method of the metal co-doped solid solution opacifier powder includes the following steps: Prepare the precursor solution; The prepared precursor solution is thoroughly stirred and reacted to form a sol. The sol is heated and kept at a constant temperature, then evaporated and dried to form a gel. The obtained gel was calcined, then ground and sieved to obtain uniformly sized metal co-doped solid solution opacifier powder.

4. The heat-insulating powder for box-type insulation of a nuclear reactor thermal system according to claim 1, characterized in that, The inorganic heat-insulating powder includes any one or a combination of several of the following: perlite, vitrified microspheres, and perlite.

5. A heat-insulating powder for box-type insulation of a nuclear reactor thermal system according to claim 1 or 2, characterized in that, The average particle size of the nano-silica aerogel is no greater than 50 nm, and the specific surface area is no less than 200 m². 2 / g, thermal stability temperature not lower than 500℃.

6. The heat-insulating powder for box-type insulation of a nuclear reactor thermal system according to claim 1, characterized in that, It also includes radiation shielding powder.

7. The heat-insulating powder for box-type insulation of a nuclear reactor thermal system according to claim 6, characterized in that, The radiation shielding powder includes any one or a combination of boron carbide, boron nitride, tungsten powder, and bismuth oxide.

8. A heat-insulating powder for box-type insulation of a nuclear reactor thermal system according to claim 1 or 3, characterized in that, The metal co-doped solid solution opacifier powder is titanium oxide powder that has been elementally doped.

9. The heat-insulating powder for box-type insulation of a nuclear reactor thermal system according to claim 8, characterized in that, The doping elements include any one or more of nickel, lanthanum, iron, barium, tungsten, zinc, magnesium, and cobalt.

10. A method for preparing the heat-insulating powder for box-type insulation of a nuclear reactor thermal system according to any one of claims 1 to 9, characterized in that, The heat-insulating powder material for box-type thermal insulation is obtained by uniformly mixing nano-silica aerogel, metal co-doped solid solution opacifier powder, inorganic heat-insulating powder, and radiation shielding powder.

Citation Information

Patent Citations

  • Preparation method of inorganic thermal insulating powder

    CN102627947A

  • Organic silicon composite material with neutron shielding efficiency and heat insulation efficiency and preparation process

    CN113563724A

  • Vacuum heat insulating material and method of using vacuum heat insulating material

    JP2005024038A